Laboratory techniques - Image processing tools on physical model tests - Hugo Guedes Lopes (2013)
This work is part of the DESTAQ project (Development of advanced techniques to measure the velocities and study the interaction between detached breakwaters and harbour structures) and aims to analyse the hydrodynamic behaviour of a detached structure as a protection element of a main rubble mound breakwater using laboratory tools and techniques. The hydrodynamic analysis that is presented includes image processing tools, and the use of the numerical model IH-2VOF. A comparison between the results obtained with both techniques is made.